Pengaruh Perceived Value Terhadap Behavioral Loyalty melalui Customer Satisfaction Sebagai Variabel Pemediasi pada Pengguna Credit Card Co-Branding Bank Aceh - Dhian Wahyuni; Ihsanuddin Ihsanuddin (Universitas Samudra, 2019)
The main objectives of the study is to analyze the effect of perceived value on customer satisfaction and its impact on the behavioral loyalty of users co-branding credit card of Bank Aceh Syariah. The research sample are 250 customers taken by random sampling. Data collection uses a questionnaire, and then the data is analyzed by statistical means of path analysis. The study found that perceived value has a positive and significant effect on customer satisfaction and behavioral loyalty. Customer satisfaction also has a positive and significant effect on behavioral loyalty. The existence of customer satisfaction strengthens the influence of perceived value on behavioral loyalty. The effect of mediating customer satisfaction in mediating the functional relationship between the two variables is partial mediation.